An overview of seven national high performance coach education programs - Callary, B.; Culver, D.; Werthner, P.; Bales, J. (International Sport Coaching Journal, 2014)
High quality education programs across the globe could help coaching move forward as a profession. Although there have been suggestions to improve sports coaching education programs by integrating theory and practice through alternative learning approaches such as mentoring and critical reflection (Armour, 2010; Cushion, Armour, & Jones, 2003), it is unclear whether such approaches have been implemented in coach education programs and how different countries are educating their coaches. The purpose of this paper is to describe how seven high performance coach education programs are educating coaches and to what extent they are employing alternative learning approaches. The goals, curricula, and pedagogical approaches are described and implications for the professionalization of coaching are discussed.